The Development of a Digital Marketing System for a Textile Business Based on a Website using User-Centered Design Approach (Case Study: Eka Jaya Tekstil) - Eko Wahyudi; Tresna Maulana Fahrudin; Faisal Ashari; Nabilah Selayanti; Agung Mustika Rizki (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
Offline product marketing has not been able to reach a wide range of target customers amidst the intensive use of the internet and social media by people in Indonesia. The competitiveness of business product sellers to acquire customers is increasingly competitive, especially during and after Covid-19, with various strategies using supporting technology such as social media and e-commerce. Eka Jaya Tekstil, as a company that operates in textile business products, has also adapted by expanding product marketing not only offline, but also through website-based product digitization. In developing a digital marketing system for textile business products, a User Centered Design approach is used where the system is developed by emphasizing user needs starting from identifying user needs, determining the context of use, determining requirements, creating solution designs, and evaluating the design against user needs. The website-based product digital marketing system that has been developed has succeeded in presenting Eka Jaya Tekstil's profile as a company that produces textile business products, production house galleries, offers superior products, and orders products. The system that has been developed involving 30 respondents using Likert scale by comparing the results of the initial and final evaluations, an increase in the average System Usability Scale (SUS) score by 6.34 points was observed. There was an improvement in the acceptable range from marginal high to acceptable, a shift in the grade scale from D to C, and the adjective rating remained Good. This indicates the success of the redesign using the UCD method in meeting user needs.